Maternal Risk Factors for Neonatal Asphyxia Among Low-Birth-Weight Infants in Kalabahi - Lapenangga, Oristha Nelzin; Ob-Adang, Gottfrieda P. Taeng; Jannah, Insani Fitrahulil; Tunggal, Dief (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Neonatal asphyxia is one of the leading causes of neonatal mortality, particularly among infants with low birth weight (LBW). At Kalabahi Regional Hospital (RSD Kalabahi-Alor), the number of LBW and neonatal asphyxia cases increased during the 2021–2024 period. This condition represents a major health concern because it may result in damage to vital organs and even death if not managed promptly and appropriately. This study aimed to analyze factors associated with the incidence of neonatal asphyxia among LBW infants at RSD Kalabahi-Alor. An observational analytic study with a retrospective case-control design was conducted using medical records of 150 LBW infants during the 2021–2024 period. The sample consisted of 50 cases with neonatal asphyxia (total sampling) and 100 controls without asphyxia (consecutive sampling), with a 1:2 case-control ratio. Data were analyzed using univariate and bivariate analyses (Chi-square test). Bivariate analysis showed that maternal age was significantly associated with neonatal asphyxia among LBW infants (p = 0.022; OR = [insert OR]; 95% CI = [insert 95% CI]). In contrast, maternal parity (p = 0.728), gestational age (p = 0.729), and history of preeclampsia/eclampsia (p = 0.465) were not significantly associated with neonatal asphyxia. These findings indicate that maternal age is significantly associated with neonatal asphyxia among LBW infants. Since only bivariate analysis was performed, the reported association has not been adjusted for potential confounding factors, and no independent risk factors can be concluded from this study. However, maternal parity, gestational age, and history of preeclampsia or eclampsia were not significantly associated with neonatal asphyxia.